EXPLORING THE PROTAGONIST’S SUFFERING IN DENNIS BOCK’S THE ASH GARDEN - Ananda, Tristi; Suhadi, Muhammad Fatih (JOURNAL OF LANGUAGE, 2025)
This research explores the multidimensional suffering of the protagonist, Emiko Amai, in Dennis Bock’s novel The Ash Garden, using Quilao’s theoretical framework on human suffering. Through a descriptive qualitative approach, the study identifies five types of suffering—physical, psychological, social, existential, and ethical—as reflected in Emiko’s experiences before, during, and after the Hiroshima bombing. The analysis highlights how Emiko, as a war survivor, embodies the traumatic effects of violence, displacement, and physical disfigurement. Her journey reveals not only the pain and isolation endured in the aftermath of war but also the gradual process of resilience and self-redefinition. Emiko’s coping strategies—both physical and psychological—demonstrate how human beings attempt to restore meaning and identity in the face of profound loss. By situating her suffering within a literary and humanistic context, this study contributes to the discourse on trauma narratives and deepens the understanding of war-induced suffering in postmodern literature.